Retrieving Malay translated Al-Quran by using N-grams with relevance feedback / Nurafzan Mohammad - Mohammad, Nurafzan (2004)
Information Retrieval is one of the fields in information technology that perform a task to search effectively and efficiency. This project is broad the study on the information retrieval. To ensure retrieving the information works effectively, relevance feedback technique implement in this project. Relevance feedback technique help to reduce uncertainty of documents retrieve by incorporating user's feedback in the system. Where the result is retrieved based on user judgment instead of computer generated result. This project also employs bigram algorithm as a retrieval method that is used to retrieve the relevant al-Quran documents based on user's query.